The Longman anthology of British literature - Damrosch, David (Longman, 2009)
The Longman Anthology of British LIterature was the first collection to pay sustained attention to the contexts within which literature is produced, even as it broadened the scope of that literature to embrace the full cultural diversity of the British Isles